Microbial Necromass in Soils—Linking Microbes to Soil Processes and Carbon Turnover - Kästner, M.; Miltner, A.; Thiele-Bruhn, S.; Liang, C. (Frontiers in Environmental Science, 2021)
The organic matter of living plants is the precursor material of the organic matter stored in terrestrial soil ecosystems. Although a great deal of knowledge exists on the C turnover processes of plant material, some of the processes of soil organic matter (SOM) formation, in particular from microbial necromass, are still not fully understood. Recent research showed that a larger part of the original plant matter is converted into microbial biomass, while the remaining part in the soil is modified by extracellular enzymes of microbes. At the end of its life, microbial biomass contributes to the microbial molecular imprint of SOM as necromass with specific properties. Next to appropriate environmental conditions, heterotrophic microorganisms require energy-containing substrates with C, H, O, N, S, P, and many other elements for growth, which are provided by the plant material and the nutrients contained in SOM. As easily degradable substrates are often scarce resources in soil, we can hypothesize that microbes optimize their carbon and energy use. Presumably, microorganisms are able to mobilize biomass building blocks (mono and oligomers of fatty acids, amino acids, amino sugars, nucleotides) with the appropriate stoichiometry from microbial necromass in SOM. This is in contrast to mobilizing only nutrients and consuming energy for new synthesis from primary metabolites of the tricarboxylic acid cycle after complete degradation of the substrates. Microbial necromass is thus an important resource in SOM, and microbial mining of building blocks could be a life strategy contributing to priming effects and providing the resources for new microbial growth cycles. Due to the energy needs of microorganisms, we can conclude that the formation of SOM through microbial biomass depends on energy flux. However, specific details and the variability of microbial growth, carbon use and decay cycles in the soil are not yet fully understood and linked to other fields of soil science. Here, we summarize the current knowledge on microbial energy gain, carbon use, growth, decay, and necromass formation for relevant soil processes, e. g. the microbial carbon pump, C storage, and stabilization. We highlight the factors controlling microbial necromass contribution to SOM and the implications for